NEW PLANTS FROM THE UPPER PALEOCENE CROSS VALLEY-WIMAN FORMATION, MARAMBIO (=SEYMOUR) ISLAND, ANTARCTIC PENINSULA (Ameghiniana, 2025)
The Cross Valley-Wiman Formation is characterized by a rich flora of compressions and petrifications, preserving leaves and seeds at its uppermost section (Bahía Pingüino Allomember), which is late Paleocene (C25n, Thanetian) in age. The fossil plant record of the Cross Valley-Wiman Formation was described by Dusén (1908), who documented at least 87 leaf taxa. Despite its importance in the Southern Hemisphere, a few studies have added some revisions to this macroflora. New Argentine fieldwork has recognized the 26 previously known leaf fossil taxa, identified two leaf taxa described by Dusén (1908), and established a record for 12 new taxa. In this work, we have added three new fern taxa (Hymenophyllaceae and Dryopteridaceae-Dryopteridoideae), three new members of Liliales (Potamogetonaceae, Ripogonaceae, and an indet. monocot form), four new non-monocot angiosperm leaf morphotypes, and two new angiosperm propagules. This raises to 53 the number of known leaf taxa for the Cross Valley-Wiman Formation. The new unbiased collection of 159 identified specimens has allowed us to quantify the relative abundance of taxa and recognize the dominance of ferns (Cladophlebis and Sphenopteris), followed by Atherospermataceae, Lauraceae, Moraceae, and Winteraceae. The presence of five Nothofagus leaf species is recognized, although at a low percentage in the flora (not dominant). The Cross Valley-Wiman Formation exceeds the Angiosperm richness of known Patagonian Paleocene leaf floras and provides new elements for Gondwana. Based on recognized taxa and their relative abundance, the upper Paleocene (upper Thanethian) flora of the continental margin of the James Ross Basin would have developed as a temperate rainforest.